히트파이프와 공기측 핀의 자연대류를 이용한 데스크톱 PC 냉각 시스템에 관한 실험적 연구 - 민병선(Byeong-Sun Min); 조호성(Ho-Seong Cho); 남경원(Kyeong-Won Nam); 박창용(Chang Yong Park) (한국생산제조학회지, 2020)
In this study, the forced convection electronics cooling systems in a desktop PC were replaced with a natural convection cooling system, and their cooling performance was compared experimentally. The natural convection cooling system consisted of a cooling block, cooling plate-fin assembly, and heat pipes. With this system, the operating temperature of the CPU (Central Processing Unit) was higher than that with the forced convection system owing to the lack of cooling capacity caused by the limited installation location and space. However, the properly designed natural convection cooling system for the GPU (Graphics Processing Unit) provided sufficient cooling capacity and the lower GPU operating temperature than that with forced convection under both idling and maximum calculation load conditions. The electric power consumption of the PC with the natural convection cooling system was at least 12.1% lower than that with forced convection. KCI Citation Count: 0